Al-Tahlil al-Dalālī Lilafẓi al-Khairi fī al-Qur’ān al-Karīm ‘inda Wahbah al-Zuhailī - Wulandari, Yusrina Dyah; Nur, Annisa Khairan (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The purpose of this research is to find out the semantics meaning and interpretation of the word al-khair according to Wahbah az-Zuhaili. This study uses a type of library research, where the discussion and interpretation of the verses of the Qur'an are studied from books and library documentation which has an object according to the study's title. The research method used is descriptive to collect comprehensive data on the data needed by the author, then compile it using primary and secondary data. The method of analysis is by analyzing and drawing conclusions and the values ​​obtained after studying the verses of al-khair according to Wahbah az-Zuhaili. The result of the analysis semantics of al-khair words in terms of the Qur’an says that its action in the world is all good deeds between the servant and His Lord. At times, the term 'al-khair' in the Quran means all the worldly benefits that people desire.Then, it is followed by the meaning of reward, indicating the rewards from Allah. Other times, the term 'al-khair' comes with the meaning of one of the blessings in this world, and blessings refer to the rewards in the Hereafter.